IMPACT ON EMPLOYEES DURING PANDEMIC BASE ON LABOR SYSTEM PERSPECTIVE - Flambonita, Suci; Ernaningsih, Wahyu; Novianti, Vera (Nurani, 2021)
The fourth paragraph at the opening of the Constitution of the Republic of Indonesia states that the Government of the Republic of Indonesia is obliged to protect the entire Indonesian nation, promote the general welfare, and educate the nation's life which is a manifestation of the responsibility of the state which is obliged to create welfare for its people fairly and equitably equally. This constitutional mandate is spelled out in the form of regulations aimed at preventing injustice from the stronger party against the weaker party so that a just and peaceful society can be created. The method used to analyze this problem is through normative and empirical mix and match. The approach used in this study is a statute approach, conceptual approach, and case approach. Legal protection for workers is an obligation for the fulfillment of basic rights inherent and protected by the constitution as regulated in Article 27 paragraph (2) of the 1945 Constitution of the Republic of Indonesia. The logical consequence of this mandate is the birth of the State's obligation to accommodate facilities and the widest possible opportunity for the community so that they can get a job as well as make it something worthy of humanity. Thus, the violation of basic rights guaranteed by the constitution is a violation of human rights. Protection of workers is regulated in Articles 67 to 101 of the Manpower Law, including those concerning wages and welfare. However, when faced with the COVID-19 pandemic situation, the company immediately provided a force majeure reason to avoid paying severance pay for workers/laborers affected by layoffs. The problem that occurs, in this case, is the termination of employment carried out by companies using force majeure reasons by companies in Indonesia unilaterally. Keywords: Impact, Employees, Pandemic